2003
DOI: 10.1001/jama.290.23.3081
|View full text |Cite
|
Sign up to set email alerts
|

A Practice-Based Intervention to Enhance Quality of Care in the First 3 Years of Life

Abstract: ROVIDING QUALITY PEDIATRIC care for young children involves matching the needs and expectations of families with the organizational structure and clinical practices of pediatric providers. There is growing evidence of deficiencies in the quality of health care for children, including low rates of preventive services, 1 persistent disparities in health status, 2 and lack of a usual source of care among ethnic and racial minorities and children in low-income families. 3 Specific limitations have been noted in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
182
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 200 publications
(185 citation statements)
references
References 26 publications
2
182
1
Order By: Relevance
“…43 The Commonwealth Fund's Healthy Steps intervention included home visiting by masters-level healthy development specialists with significant gains in the quality of well-child care, although the multifactorial nature of this intervention made it difficult to evaluate the effectiveness of the home-visiting component. [44][45][46] A South Carolina study showed that a program that linked school-based home visitors to group well-child visits resulted in greater retention of anticipatory guidance and improved satisfaction with care. 47 These initiatives provide a glimpse into the potential of linking home visitors with the pediatric medical home.…”
Section: Benefits Of Home-visiting Programsmentioning
confidence: 99%
“…43 The Commonwealth Fund's Healthy Steps intervention included home visiting by masters-level healthy development specialists with significant gains in the quality of well-child care, although the multifactorial nature of this intervention made it difficult to evaluate the effectiveness of the home-visiting component. [44][45][46] A South Carolina study showed that a program that linked school-based home visitors to group well-child visits resulted in greater retention of anticipatory guidance and improved satisfaction with care. 47 These initiatives provide a glimpse into the potential of linking home visitors with the pediatric medical home.…”
Section: Benefits Of Home-visiting Programsmentioning
confidence: 99%
“…Current research has shown that the adoption of new technologies that allow for patient transactions outside the primary care office can significantly affect the effectiveness, patient-centeredness, timeliness, and efficiency of child development and health promotion practice. [6][7][8][9][10] The potential benefits of this type of technology for WCC are considerable. If developmental and psychosocial screening can be accomplished through non-face-to-face transactions over the Internet and communicated to the PCP before the visit, the PCP can ensure that the specific needs of the family are met during the WCC visit in an efficient and effective manner.…”
Section: Introductionmentioning
confidence: 99%
“…Proposals to improve WCC delivery include changes such as utilizing group visits, incorporating nonphysician child developmental specialists into the visit, and instituting standardized screening by nonphysician staff. [8][9][10] Although practice redesign in large, integrated delivery systems has been described, 11,12 smaller practices with #5 physicians provide most primary care. 13 Additionally, community health centers (CHCs) are a critical source of primary care for children in low-income communities.…”
mentioning
confidence: 99%